Strategi Pengembangan Ekowisata Mangrove Berbasis Analisis Ifas-Efas: Studi Kasus Taman Edukasi Mangrove Purworejo - Asiah Munawaroh; Lilik Kartika Sari; I Gede Suweda Anggana Putera (Universitas Mataram, 2026)
Demang Gedi Mangrove Education Park (TEM) in Purworejo Regency holds significant natural resource potential; however, it faces challenges such as declining visitor numbers and management constraints. This study aims to analyze the ecological condition of the mangrove forest by examining mangrove density and to formulate appropriate ecotourism development strategies using the IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) matrix approach. The research methodology involved field surveys to collect vegetation density data, alongside interviews and questionnaires for SWOT analysis. The results indicate that the ecological condition of the mangrove forest is classified as 'very good,' with vegetation density ranging from 3,466 to 4,366 ind/ha. Based on the strategic analysis, the development position of TEM Demang Gedi is located in Quadrant I (Growth-Oriented Strategy). This position indicates that the area possesses strong internal strengths to capitalize on existing external opportunities. The recommended priority strategy is a progressive strategy, specifically maximizing natural potential and government support to develop sustainable conservation-based educational tourism.